Legal Analysis of Direct Cash Assistance (BLT) Policy for Achieving Social Welfare - Pera Pera; Endang Sutrisno; Harmono Harmono (Asian Journal of Social and Humanities, 2026)
People’s welfare is a primary objective of state administration, which is pursued through various social protection policies, including the Direct Cash Assistance (Bantuan Langsung Tunai [BLT]) program. Although the poverty rate has continued to decline, vulnerable populations still experience economic pressure due to increasing living costs. Therefore, effective and targeted policy interventions are required. This study aims to examine the implementation of the Direct Cash Assistance (Bantuan Langsung Tunai [BLT]) policy in improving community welfare based on Cirebon Regent Regulation Number 71 of 2023 concerning the Social Welfare Center (Pusat Kesejahteraan Sosial [Puskesos]) and to evaluate its effectiveness and targeting accuracy. This study employed a normative juridical approach with a qualitative research design. The results showed that the implementation of Direct Cash Assistance (Bantuan Langsung Tunai [BLT]) in Cirebon Regency was generally consistent with applicable legal provisions through stages of beneficiary data collection, verification, validation, and assistance distribution involving the Social Welfare Center (Pusat Kesejahteraan Sosial [Puskesos]). However, the policy has not been fully effective because the assistance remains primarily consumptive in nature and challenges persist regarding the accuracy and improvement of the beneficiary data system. Therefore, improvements are needed in data management systems, implementer capacity, optimization of the Puskesos role, and strengthening of economic empowerment programs to achieve sustainable social welfare.